Designing A Low Angle X-Ray Scattering (Laxs) System And Its Use In Characterisation Of Some Biomedical Materials - Hussein, Nagi Abdallah (2004)

(untitled)
Serakan foton sinar-X yang bertenaga diagnostik «140 keY), pad a sudut serakan keeil «12° ), daripada bahan Z rendah, seeara umumnya berbentuk koheren. Ciri kekoherenan ini akan membawa kepada kesan interferens antara foton-foton yang terserak itu untuk menghasilkan eorak belauan yang mempunyai kaitan dengan struktur antara-atom dan struktur antara-molekul medium serakan. Scattering of X-rays photons from low Z materials at diagnostic energies « 140 ke V) and low scattering angles «12°) is mainly coherent in nature. This coherence property will lead to interference effects between these scattered photons resulting in diffraction patterns, which are related to the interatomic and intermolecular structure of the scattering medium.